PRIVATE PRISONS AND PENITENTIARY SYSTEM OF THE REPUBLIC OF SERBIA - Milić, Ivan; Dimovski, Darko (Zbornik radova Pravnog fakulteta u Novom Sadu, 2015)
The authors, starting from reasons such as lack of accommodation capacities for all inmates, the necessity of securing the labor needs of prisoners and saving money, said that there is the possibility of granting licenses to private companies to enter with their financial resources in the penitentiary system of the Republic of Serbia. After that, the authors list the various models of privatization of prisons, while analyzing the advantages and disadvantages of each model individually through the issue of legitimacy, cost of operation (semi) private prisons, rates of return, the level of security and quality of service. At the end the authors, looking at each of these issues through the prism of the functioning of the prison in the Republic of Serbia, said that the privatization model prison most compatible to our penitentiary system.